French Muslims in Perspective Nationalism, Post-Colonialism and Marginalisation under the Republic - Downing, Joseph; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
With the largest Muslim population in Western Europe, France has faced a number of critiques in its attempts to assimilate Muslims into an ostensibly secular (but predominantly Catholic) state and society. This book challenges traditional analyses that emphasise the conflict between Muslims and the French state and broader French society, by exploring the intersection of Muslim faith with other identities, as well as the central roles of Muslims in French civil society, politics and the media. The tensions created by attacks on French soil by Islamic State have contributed to growing acceptance of the Islamophobic discourse of Marine Le Pen and her far-right Front National party, and debates about issues such as headscarves and burkinis have garnered worldwide attention. Downing addresses these issues from a new angle, eschewing the traditional us-and-them narrative and offering a more nuanced account based on people's actual lived experiences. French Muslims in Perspective will be of interest to students and scholars across sociology, politics, international relations, cultural studies, European Studies and French studies, as well as policy makers and practitioners involved in immigration, education, and media. .
1. Introducing 'French Muslims' and Banality: Beyond Essentialism, Exceptionalism and Saslaciousness -- 2. Many Republics, Many Solitudes: Europeanisation, Politics, Islam, Ethnicity and the State in France -- 3. Liberating France from Fascism and Upholding Civil Liberties: French Muslims Soldiering and Policing for the Republic -- 4. Confronting Orientalism, Colonialism and Determinism: Deconstructing Contemporary French Jihadism -- 5. Gender, Orientalism and Muslims in France: Culture, Masculinity, Violence and Sexuality -- 6. The Cultural Paradoxes of Frenchness: Cultural Nationalism, Social Boundaries and French Muslims in Broader Discursive Perspective -- 7. Conclusions on French Muslims. .
Keywords: Islam; Political sociology; Race; Social structure; Equality; Europe -- Politics and government; Islam; Political Sociology; Race and Ethnicity Studies; Social Structure; European Politics